1989
DOI: 10.1115/1.3250745
|View full text |Cite
|
Sign up to set email alerts
|

Framework for a Unified Model for Nucleate and Transition Pool Boiling

Abstract: An area and time-averaged model for saturated pool boiling heat fluxes has been developed. In the model, which is valid in the upper end of nucleate boiling and in transition boiling, the existence of stationary vapor stems at the wall is assumed. The energy from the wall is conducted into the liquid macro/micro thermal layer surrounding the stems and is utilized in evaporation at the stationary liquid–vapor interface. The heat transfer rate into the thermal layer and the temperature distribution in it are det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
63
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(70 citation statements)
references
References 0 publications
5
63
0
Order By: Relevance
“…Furthermore, Dhir and Liaw [21] found that during pool boiling, α dry (T w ≈ Τ Ν ) varies between 0.68 and 0.8 when contact angles vary between 27 and 90 degrees respectively.…”
Section: Physics Of Boilingmentioning
confidence: 99%
“…Furthermore, Dhir and Liaw [21] found that during pool boiling, α dry (T w ≈ Τ Ν ) varies between 0.68 and 0.8 when contact angles vary between 27 and 90 degrees respectively.…”
Section: Physics Of Boilingmentioning
confidence: 99%
“…First, nucleation sites in appropriate number and dimensions need to be provided such as cavities, rough areas or hydrophobic islands 2 . As of today, the performance of boiling surfaces has been increased by using wicking structures to prevent dry out 3 , by increasing the surface area with fins or fluidized bed [3][4][5][6] , and by enhancing the wettability of the surface [5][6][7][8][9] . The latter strategy is justified by experiments of Wang and Dhir 10 , showing that the CHF was increased by enhancing surface wettability.…”
mentioning
confidence: 99%
“…Such modification generally increases surface wettability, which causes an increased CHF through the enhanced liquid spreading over the heated area. 14,15 Another effect of the surface modification is to increase the number of microscale cavities, which serve as the starting sites for heterogeneous nucleation of liquid for bubble formation. 1,2 The relevant sizes of such cavities are generally in the range of tens to hundreds of micrometers.…”
mentioning
confidence: 99%